CAUSES OF DIFFERENT PROFITABILITY OF AGRICULTURAL SECTOR - Vučković, Branko (Economics of Agriculture, 2016)
This work involves identifcation of causes of different proftability of agricultural sector done on case study of nearly identical agricultural enterprises. It shows that fnancial mix even in scope of similar companies can lead to various proft indicators. Through comparative fnancial analysis in the same industry and activity by applying methods and techniques we have concluded that company PP Ratkovo operates more stable and closer to determined norms and also shows better results in majority of the indicators. Horizontal and vertical analysis indicates that companies in Agribusiness partner group use expensive external sources of fnancing. We have precisely defned in which cost segment occurs highest distinction. Also we have shown reasons why PP Ratkovo in the last two years manifests great proftability measured by ebit, ebitda and net proft as well as excellent structure of material costs and wages costs in in frame of the operating income, and reasons why enterprises in Agribusiness partner group does not.